PELATIHAN PRODUKSI GULA SEMUT UMKM DI DESA SENDANG BARU LAMPUNG TENGAH - Tina Miniawati Barusman; Andala Rama Putra Barusman; M Yusuf S Barusman; Hendri Dunan; Niki Agus Santoso (LP4MK STKIP PGRI Lubuklinggau, 2023)
The background of this community service program is the use of register forests in Sendang Baru Village, Sendang Agung District, Central Lampung Regency, where the register forests are used by the local community to process sap trees found in the forest to be processed into various kinds of sugar. The forest management system aims to empower the community (increase economic value, cultural value, provide benefits to the managing community and local community). . This production training The participants of the Sendang Baru Village community were given material presentation and socialization on optimization in processing palm sugar into ant sugar or palm powder sugar. Introduced the tools and materials used for the processing of ant sugar production, as well as how to operate a sap mixer for the sap coagulation process into sugar and an oven machine for the ant sugar drying process. Ant sugar training participants practice the process of making ant sugar according to what has been demonstrated.